2013
DOI: 10.2166/wp.2013.205
|View full text |Cite
|
Sign up to set email alerts
|

Managerial response to sea level rise in the tidal estuaries of the Indian Sundarbans: a geomorphological approach

Abstract: Tidal estuaries constrained by embankments in the Sundarbans have failed to respond to a .1 m sea level rise over the past 100 years since their construction. This paper shows that this has led to a disequilibrium morphology leading to channel erosion that has undermined embankments, causing mass failure, breaching and subsequent flooding during surge events. Predicted future sea level rise will exacerbate this trend and managed realignment of embankments will be needed to accommodate it. Management practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Perhaps the most important data required is for tidal and surge information, however such data are almost entirely absent at the moment (Bhattacharyya et al, 2011 It was observed that tidal range along the Sundarbans estuaries vary from place to place within the estuary. On an average, tidal fluctuation in Sundarbans estuary is around 5 meters depending on the lunar cycle, as is evident from the Figure. 2.…”
Section: Hydrodynamic Parameters and Their Significancementioning
confidence: 99%
“…Perhaps the most important data required is for tidal and surge information, however such data are almost entirely absent at the moment (Bhattacharyya et al, 2011 It was observed that tidal range along the Sundarbans estuaries vary from place to place within the estuary. On an average, tidal fluctuation in Sundarbans estuary is around 5 meters depending on the lunar cycle, as is evident from the Figure. 2.…”
Section: Hydrodynamic Parameters and Their Significancementioning
confidence: 99%
“…These channels reflect an almost exclusively tidal-105 driven geomorphology, with sediments and discharge from the main G-B rivers no longer 106 entering the western delta front (Allison, 1998b;Bhattacharyya et al, 2013). 107…”
Section: Background To the Indian Sundarbans 83mentioning
confidence: 99%
“…In addition to eustatic SLR, relative SLR in the Indian Sundarbans is influenced primarily by land subsidence, e.g. from auto-compaction, tectonic activity and anthropogenic processes, including groundwater withdrawals (Bhattacharyya et al, 2013). Further information on land subsidence contributing to SLR, as well as challenges resulting from the limited relevant data in the Sundarbans, is given in the supplemental material.…”
Section: Challenges Faced By Sundarbans Residentsmentioning
confidence: 99%
“…Some of the technical work performed for the World Bank study has appeared in the peer-reviewed literature (e.g. Bhattacharyya, Pethick, & Sarma, 2013;Biller & Sanchez-Triana, 2013), but most of it has not.…”
Section: Introductionmentioning
confidence: 99%